Políticas públicas de inclusão de alunos com deficiência de 1994 a 2014: limites e perspectivas na inclusão de alunos surdos no município de Colombo-PR - Neves, Regiane Timoteo das (2016)
This thesis has as its search goal the study of public policies for the inclusion of disabled students and the inclusion of deaf students from 1994 to 2014. It addresses the limits and perspectives towards the inclusion of deaf students in the city of Colombo-PR. Furthermore, it believes that the rights recognition for those who feel oppressed cannot work as law enforcement, but formed in coexistence and values assimilation. It is essential to emphasize the importance of this issue, although it has been heavily researched and documented. The inclusion process is dynamic and requires a continuous research work to create a solid theoretical basis for reflections and actions that contribute towards the inclusion process of students with disabilities, particularly deaf students at Elementary Schools. This work aimed to investigate how public policies have been implemented, mainly with deaf students, based on the Brazilian educational context until its application in the city of Colombo-PR before its definition and operational factors of its proposals dated from 1994 to 2014. To guide the sequence of this work it was listed as general objective: the investigation of the public policies with regards to the inclusion of students with disabilities and the results of the inclusion of deaf students within the contradictions presented in regular schools; Specific objectives: Explain the context of exclusion / inclusion that characterizes the modern society; analyze official documents formally drawn up from 1994 to 2014 which have legally supported the inclusion process in Brazil; analyze public policies with regards to the inclusion of deaf students from their historical and educational background and investigate the process of inclusion of deaf students in the city of Colombo-PR. For this research, the legal documents that support public policies for inclusive education in Brazil will be used. It was also performed a literature research that contextualizes some historical and ideological conceptions of public policies for the process of inclusion, mainly to deaf students from 1994 to 2014. In order to collect data, it was performed non-directive interviews. To understand the contradictions in the inclusive process of students with disabilities in the Brazilian regular schools, it was used the historical materialism method because it provides a critical reflection between what is presented in public policy and the reality found at Elementary Schools.